Emigration and democracy - Docquier, Frédéric (The World Bank, 2011)
Migration is an important yet neglected determinant of institutions. This paper documents the channels through which emigration affects home country institutions and considers dynamic-panel regressions for a large sample of developing countries. The authors find that emigration and human capital both increase democracy and economic freedom. This implies that unskilled (skilled) emigration has a positive (ambiguous) impact on institutional quality. Simulations show an impact of skilled emigration that is generally positive, significant for a few countries and for many countries once incentive effects of emigration on human capital formation are accounted for